Cultural evolution & genre : an investigation of three graphic narratives of the South African Border War (1975-1988) - Du Plessis, Daniel Marthinus (Stellenbosch : Stellenbosch University, 2012)
Stellenbosch University. Faculty of Arts and Social Sciences. Dept. of Visual Arts